Engineering the common cold to be a live-attenuated SARS-CoV-2 vaccine - Kasman, Laura M. (Frontiers in Immunology, 2022)
According to the American Centers for Disease Control and Prevention, people in all age groups catch two or more “colds” per year, at least half of which are caused by human rhinoviruses. Despite decades of effort, there are no vaccines or drugs against rhinovirus infections and even social distancing measures that were effective in reducing the spread of the pandemic coronavirus, SARS-CoV-2, did not reduce the rate of rhinovirus detection. Fortunately, most rhinovirus strains are naturally attenuated in that they are not associated with serious illness, hospitalization or mortality. Instead, rhinoviruses are one of the most frequent viruses found in nasal swabs of asymptomatic, healthy people. Since rhinovirus infections cannot be avoided, a rational approach would be to engineer them for the benefit of their human hosts. Rhinovirus infections naturally induce robust mucosal and serum immune responses to all virus-expressed proteins. Several replication-competent, human rhinovirus vaccine vectors able to express protective antigens for other pathogens have already been designed and tested in animal models. With this strategy, the inevitable common cold would be able to induce immunity not just to a specific rhinovirus serotype but to other more pathogenic respiratory viruses as well. This article reviews existing rhinovirus vaccine vector technology and describes the characteristics that make live-attenuated rhinoviruses attractive vaccine candidates for SARS-CoV-2 and other pathogenic respiratory viruses in the future.